Targeting food security interventions: The case of Ethiopia’s productive safety net programme - Coll-Black, Sarah; Gilligan, Daniel O.; Hoddinott, John F.; Kumar, Neha; Taffesse, Alemayehu Seyoum; Wiseman, William (International Food Policy Research Institute, 2013)
The Productive Safety Net Programme (PSNP) is targeted towards households that are both food-insecure and poor. Overall the targeting principles laid out in the Project Implementation Manual are being followed, but with some regional variation. Over time, community understanding of targeting criteria improved across most of the PSNP regions. From an international perspec-tive, the PSNP is well-targeted. The need for continuous capacity building and the level of follow-up and monitoring from higher level implementers have important implications for how well communities can target resources to the poorest.